2021
DOI: 10.48550/arxiv.2110.08560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Black holes with Lagrange multiplier and potential in mimetic-like gravitational theory: multi-horizon black holes

G. G. L. Nashed,
Shin'ichi Nojiri

Abstract: In this paper, we employ the mimetic field equations coupled with the Lagrange multiplier and mimetic potential to derive non-trivial spherically symmetric black hole (BH) solutions. We divided this study into three cases: The first one in which we take the Lagrange multiplier and mimetic potential to have vanishing value and derive a BH solution that completely coincides with the BH of the Einstein general relativity despite the non-vanishing value of the mimetic field. The first case is completely consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…Moreover, it is shown that mimetic theory can investigate the flat rotation curves of spiral galaxies [12,13]. Recently, a mimetic theory has gained a lot of attention in the domain of cosmology [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and in the domain of astrophysics [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is shown that mimetic theory can investigate the flat rotation curves of spiral galaxies [12,13]. Recently, a mimetic theory has gained a lot of attention in the domain of cosmology [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and in the domain of astrophysics [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%